Modeling Filipino teachers’ intention to use technology: a MIMIC approach - David, Adonis P.; Aruta, John Jamir Benzon R * (Taylor and Francis, 2022)
Determining factors of teachers’ intention to use technology is important. Drawing from the Technology Acceptance Model (TAM), we tested a research model depicting the direct and indirect effects of teachers’ age, gender, perceived ease of use, perceived usefulness, and attitude towards use of technology on their behavioral intention to use technology. Using data from a self-report questionnaire used in the survey of 402 Filipino basic education teachers, a Multiple Indicators Multiple Causes (MIMIC) analysis was performed. Results indicate that age, perceived ease of use, perceived usefulness, and attitude towards use have influence on teachers’ intention to use technology. Implications of the results are discussed.